Demon slayer = Kimetsu no yaiba. Volume 10, Human and demon - Gotoge, Koyoharu, 1988-; Stan!, 1964- (Shonen Jump manga., 2020)
"In Taisho-era Japan, Tanjiro Kamado is a kindhearted boy who makes a living selling charcoal. But his peaceful life is shattered when a demon slaughters his entire family. His little sister Nezuko is the only survivor, but she has been transformed into a demon herself! Tanjiro sets out on a dangerous journey to find a way to return his sister to normal and destroy the demon who ruined his life ... Despite some comic misunderstandings that almost blew their cover, Tanjiro, Inosuke, and Zenitsu have smoked out Daki, a demon that has been devouring the residents of an entertainment district for years. The Hashira Tengen Uzui and his ninja companions engage Daki, but if they cannot handle her, what chance do Tanjiro and his friends have of taking on one of Kibutsuji's upper-rank demons by themselves?"--Provided by publisher